Direct Synthesis of Chain‐end‐functionalized Poly(3‐hexylthiophene) without Protecting Groups Using a Zincate Complex. Issue 11 (4th May 2020) - Inagaki, Shin; Yamamoto, Takuya; Higashihara, Tomoya
Abstract: Chain‐end‐functionalized poly(3‐hexylthiophene)s (P3HTs) with benzyl alcohol (─PhCH2 OH), phenol (─PhOH), and benzoic acid (─PhCOOH) groups are directly synthesized based on the Negishi catalyst‐transfer polycondensation method utilizing the zincate complex of t Bu4 ZnLi2 . In this system, neither protection nor deprotection steps are required, and also providing a living polymerization system to control the molecular weight while maintaining a low molar mass dispersity ( Ð M ) of the obtained P3HT derivatives. Indeed, the chain‐end‐functionalized P3HTs can be synthesized along with controlled number‐average molecular weights ( M n = 5100–20 000), low Ð M (1.06–1.14), and high chain‐end functionality (Fn = 46–86%). The Fn values for the alcohol and phenol groups are found to be high (86% for ─PhCH2 OH and 71% for ─PhOH based on 1 H NMR, respectively), as also confirmed by matrix‐assisted laser desorption/ionization time of flight mass spectroscopy. The easily synthesizable chain‐end‐functionalized P3HTs will be applicable for the facile synthesis of block and branched polymers containing P3HT as well as its related semiconducting polymer segments. Abstract : Chain‐end‐functionalized poly(3‐hexylthiophene)s (P3HTs) with benzyl alcohol (─PhCH2 OH), phenol (─PhOH), and benzoic acid (─PhCOOH) groups are directly synthesized based on the Negishi catalyst‐transfer polycondensation method utilizing the zincate complex of t Bu4 ZnLi2 . Indeed, the chain‐end‐functionalized P3HTs can be synthesized along with controlled number‐average molecular weights ( M n = 5100–20 000), low Ð M (1.06–1.14), and high chain‐end functionality (Fn = 46–86%) .